Three periods in Husserl’s study of teleology: evidence and systematicity in the theory of knowledge, - Conde, Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Husserl’s phenomenology can be apprehended on the whole as a teleology of reason which consists of the aspiration to the greatest possible rationality in the cognitive, practical-individual and practical-communitarian or historic field. Following this tripartite division this paper analyzes the appearances of this concept in several texts of Husserl’s thinking: Logical Investigations (1900-1901), Renewal of human being and of culture (1932-1937), some manuscripts of the 30’s about teleology, the Crisis (1936) and the complementary text to the Crisis number 32 «Teleology in the history of philosophy»(1936). Finally the paper deals with an introduction to a possible analysis of the divine from the concept of teleology and a discussion about how far the concept of teleology can be tackled by phenomenology or would have to be studied exclusively by theology. (1932-1937), some manuscripts of the 30’s about teleology, the